Effect of Concentration and Time of Giving Paclobutrazol on Lumbu Hijau-Garlic Seedling Bulbs - Kristina, Nilla; Gustian, Gustian; Yusniwati, Yusniwati; obel, Obel; Khairunnisa, Nadia (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2024)
The farmer's interest in garlic planting is low because the yield is unsatisfied. One reason is the use of small cloves. Giving paclobutrazol is expected to increase the size of garlic cloves and bulbs. This research aims to determine the interaction between concentration and time of giving paclobutrazol, which produces the best size for cloves and bulbs. The research is a factorial, Completely Randomized Design. The first factor is the concentration of paclobutrazol:250 mg.L-1 and 500 mg.L-1 of water. The second factor is the time of applying paclobutrazol: 6 and 10, 8 and 12, 10 and 14 weeks after planting (w.a.p). Data were analyzed using variance, which will be continued with DNMRT at the 5% level. The results showed that giving paclobutrazol at 10 and 14 w.a.p resulted in the highest apparent stem diameter and yield, but even so, the weight of the largest and the smallest cloves was the lowest. Meanwhile, giving paclobutrazol at 6 and 10 w.a.p resulted in the highest weight of the largest cloves 1.95 g and the highest of the smallest cloves 0.55 g, even though the apparent stem diameter and yield were the lowest. Treatment of 250 mg.L-1 paclobutrazol resulted in the highest weight of the largest cloves 1.80 g.